AB0738 Concordance of greyscale and powerdoppler modes in ultrasound assessment of ra: significantly better performance of the dorsal versus palmar approach to mcp and pip joints. (23rd January 2014) - Witt, M.; Müller, F.; Nigg, A.; Reindl, C.; Schulze-Koops, H.; Grunke, M.
Abstract : Background: Ultrasound (US) assessment of MCP and PIP joints in RA can be performed using a palmar and/or a dorsal approach. At the moment, there is no clear preference for either method and well-validated US scores such as the US-7 score include both approaches for a comprehensive evaluation. However, the frequency of synovitic findings seems to differ considerably depending on the approach used. Objectives: To clarify the role of palmar versus dorsal US assessment in patients with RA. Methods: Patients with newly diagnosed and therapy-naive RA were included in the study. Ultrasound was performed with grey scale (GSUS) and power Doppler (PDUS) of the MCP and PIP joints, using the dorsal and palmar approach. Synovitic findings in GSUS and PDUS were graded semiquantitatively as specified before. After the initial assessment, patients were treated according to national guidelines and were seen on a regular outpatient basis. Clinical and sonographic reevaluation was performed at month 6. Concordances of palmar and dorsal GSUS and PDUS at baseline and at month 6 were calculated as the sum of all double positive joints and double negative joints divided by all joints. Double positive joints were defined as joints with GSUS and PDUS findings, single positive joints were defined as joints with either GSUS or PDUS findings, double negative joints were defined as joints without GSUS and PDUS findings. Results: Data of 50 RA patients was available for analysis. At baseline, palmar GSUS identified synovitic findings in 27.2% of MCP and PIP joints, while dorsal GSUS was positive in 28.8% (palmar versus dorsal not significant). Palmar PDUS was positive in 4.0% of MCP and PIP joints, compared to 18.3% of positive findings with dorsal PDUS (palmar versus dorsal p < 0.05). At month 6, palmar GSUS identified synovitic findings in 31.9% of MCP and PIP joints, while synovitic findings identified with dorsal GSUS decreased to 13.9% (palmar versus dorsal p < 0.05). Palmar PDUS was positive in 3.7% of MCP and PIP joints at month 6, while dorsal PDUS was positive in 6.6% (palmar versus dorsal p < 0.05 for MCP joints). Concordances of palmar GSUS and PDUS was 0.77 at baseline, compared to 0.89 of dorsal GSUS and PDUS (palmar versus dorsal < 0.05). At month 6, concordances of palmar GSUS and PDUS was 0.70, while concordances of dorsal GSUS and PDUS was 0.93 (palmar versus dorsal < 0.05). Conclusions: We observed significant discrepancies of the performances of GSUS and PDUS depending on whether the palmar or dorsal approach was used. These discrepancies were found at two time points with different disease activities. Palmar and dorsal GSUS performed similar at baseline, but the sensitivity to change was significantly better on the dorsal side. PDUS detected significantly more signals from the dorsal side at both time points. Of note, we found that the dorsal approach yields significantly better concordances of GSUS and PDUS than the palmar approach. Assuming that "double positive" joints, i.e. joints with GSUS and PDUS findings, more specifically represent true synovitic joints than only single positive joints, the dorsal approach performs better than the palmar approach. Further analysis is needed to clarify the specific advantages and limitations of both approaches. Disclosure of Interest: None Declared